2009
DOI: 10.1657/1523-0430-41.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Limitation in the Alpine: A Meta-Analysis

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 76 publications
8
87
3
2
Order By: Relevance
“…Rather, our results seem to corroborate García-Camacho and Totland's (2009) demonstration that there is no evidence for assuming that self-compatibility in the alpine generally relieves pollen limitation. At the same time, P. halleri does not entirely reflect a clear evolutionary trajectory in line with the increased pollination probability hypothesis through increased floral display either.…”
Section: International Journal Of Plant Sciencessupporting
confidence: 87%
“…Rather, our results seem to corroborate García-Camacho and Totland's (2009) demonstration that there is no evidence for assuming that self-compatibility in the alpine generally relieves pollen limitation. At the same time, P. halleri does not entirely reflect a clear evolutionary trajectory in line with the increased pollination probability hypothesis through increased floral display either.…”
Section: International Journal Of Plant Sciencessupporting
confidence: 87%
“…In accordance with these conditions, major community studies in the South American Andes (18°S, 33°S and 50°S) have revealed an overall altitudinal decline in flower visitation rates above the tree line to the extent of a 50% decrease in pollinator availability between the two altitudinal extremes of the alpine belt (Arroyo et al 1985, Arroyo & Squeo 1990. Pollen limitation, moreover, has been reported in many alpine species (García-Camacho & Totland 2009), including for one in the lower alpine on our study sites . This general scenario fits the autogamous fertility insurance hypothesis where low or unreliable pollination service is seen to favor selfcompatibility coupled with capacity for unassisted selfpollination (Kalisz & Vogler 2003).…”
Section: Introductionsupporting
confidence: 88%
“…However, hand-pollinations did not increase seed number, suggesting environmental constraints limiting seed production in this population. Resource rather than pollen limitation for plant reproduction is not uncommon in alpine environments and has been found for numerous other alpine species (Cambell and Hamala 2003;Totland 1997;Eide 1999, see GarciaCamacho andTotland 2009 for a more general discussion). Further, Kudo and Molau (1999)found similar fertilization rates, but significantly higher seed abortion rates when comparing high elevation with low elevation populations of Astragulus alpinus L. in northern Sweden.…”
Section: Pollination Environment At Low and High Elevationmentioning
confidence: 93%
“…In high arctic and alpine environments pollinator diversity, abundance and activity is often low due to unfavorable conditions for insect life (Arroyo et al 1982(Arroyo et al , 1985Warren et al 1988;McCall and Primack 1992;Totland 1994b;Bingham and Orthner 1998;Blionis and Vokou 2001) leading to highly variable and often scarce pollination success. Because of the commonly strong pollen limitation of reproduction in alpine plants (Billings 1974;Stenström and Molau 1992;Elberling 2001;Totland and Sottocornola 2001;Lundemo and Totland 2007; but see Totland 1997;Totland and Eide 1999;Totland 2001;Garcia-Camacho and Totland 2009), flower longevity often increases with increasing elevation (Arroyo et al 1981;Primack 1985;Bingham and Orthner 1998;Blionis and Vokou 2001;Fabbro and Körner 2004;Giblin 2005;AEgisdottir and Thorhallsdottir 2006;Lundemo and Totland 2007). Contrasting results, however, due to alternative pollination strategies (Arroyo et al 2006) or specific pollinator behavior (Duan et al 2007) suggest that variation in flower longevity is highly context-dependent, but few studies have directly characterized the actual pollination environment.…”
Section: Introductionmentioning
confidence: 99%